Exploring the Impact of Ethnocentrism, and Country of Origin on Consumer Purchase Intentions: A Case Jingdezhen Blue-and-White Ceramics - Yifeng, Fang; Yaacob, Husaini Bin (South Asian Journal of Social Sciences and Humanities, 2024)
In China, the native people living in the society have great enthusiasm for their country and they always prefer using and consuming their homeland-manufactured products. Moreover, Chinese have their own culture in which they possess different arts and creative commodities consumption and purchasing to follow their traditional norms. This study investigates the patriotic nature of Chinese customers, who have a strong preference for their home-made products and cultural heritage. The research uses an empirical model to examine the relationship between animosity, ethnocentrism, country of origin, and country knowledge, as well as perceived warmth as a mediator. The study used a positivist philosophy with a deductive approach, using the S-O-R theory as the empirical support. Quantitative primary data was collected from 280 customers of blue and white ceramic products, with a total sample size of 280. The SEM technique revealed that country of origin and ethnocentrism significantly influences customer purchase intentions for ceramic products. Furthermore, the mediation analysis revealed that customer ethnocentrism indirectly impacts purchase intentions through perceived warmth. The study concludes that Chinese customers have a high devotion to their mother country’s products, and the behavior of native sellers and general society people is crucial in stimulating their purchase intentions.